Fire or Ice? A Critical Assessment of the Underlying Views - Burns, Kelly; Moosa, Imad (Journal of Reviews on Global Economics, 2013)
Abstract: A debate is raging on whether the U.S. is likely to experience hyperinflation (fire) or deflation (ice) as a result of post-crisis policies, particularly quantitative easing. Views have been put forward to suggest that the U.S. is heading towards ice, while others suggest that fire is the destination. There are also those who envisage either fire or ice, depending on how much is done to combat deflation. These views are assessed critically to reach the conclusion that, on the balance of probabilities, it seems that the U.S. is more likely heading towards fire.